Islamic copper-based metal artefacts Open Access from the Garb al-Andalus. A multidisciplinary approach on the Alcáçova of Mārtulah (Mértola, South of Portugal) - Schiavon, Nicola (2022)
A multidisciplinary approach has been applied to investigate the production technology of a collection of copperbased artefacts found during archaeological excavation campaigns carried out in the Almohad neighbourhood of Mārtulah, the Islamic name of modern Mértola (South of Portugal). In stark contrast to other Islamic materials found in the same site such as common and finely decorated pottery, glass, and bone artefacts, metal objects have received less attention despite the high number of artefacts recovered. This study focuses on the chemical characterisation of 171 copper-based artefacts dating back to the 12th and the first half of the thirteenth centuries. The artefacts are daily use objects and consist of personal ornaments (earrings, rings, and casket ornaments), tools (spindles, spatulas, and oil lamp sticks) and artefacts with unknown functions. The analytical results by X-ray fluorescence Spectroscopy (XRF) provided information not only about technological issues but infer as well on the socio-economic implications of metal consumption in Islamic Mértola. Results revealed that metals were produced using a variety of Cu-based alloys, namely unalloyed copper, brasses (Cu + Zn), bronzes (Cu + Sn), and red brasses (Cu + Sn + Zn), with a variable concentration of Pb, without any apparent consistency, as a likely result of recurrent recycling and mixing scrap metals practices or use of mineral raw materials available locally.